PENGARUH PENERAPAN MODEL SEARCH, SOLVE, CREATE AND SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 20 PADANG - ULFA TRI WAHYUNI (Jurnal Edukasi dan Penelitian Matematika, 2021)
Mathematics learning has several objectives that must be achieved. One of them is the ability to solve mathematical problems. However, in reality, the students' mathematical problem solving skills at SMPN 20 Padang are still low. Therefore, to improve students' mathematical problem solving abilities, research was carried out by applying the Search, Solve, Create, and Share (SSCS) learning model. This type of research is quasi-experimental and the research design is a randomized control group only design. Based on the results of the final test data analysis, it is concluded that the mathematical problem-solving abilities of students who learn using the Search, Solve, Create, and Share model are better than the mathematical problem solving abilities of students whose learning uses the direct learning model. Keywords — SSCS, mathematical problem solving skills